Volunteering as a Form of Students’ Educational Activities in the Context of the University’s Third Mission - Ch. I. Buyakova; I. Yu. Malkova (Высшее образование в России)
The article considers the service learning program and volunteering as relevant forms for the university’s “third mission” implementation. Volunteering in the educational process is understood as students’ gratuitous activities aimed at solving urgent social problems and designed to increase students’ social and civic activity. The article states that the volunteering has an educational resource for the development of students’ skills, which determines their professional development.As part of theoretical research, volunteering is presented as a basis and mechanism for implementing the service learning program in the context of university’s third mission. Within the framework of the service learning program, student social activity is viewed just as important as educational and research activities. The results of the research (student focus groups with experience in volunteering) aimed at identifying empirical signs of metacompetencies that are formed under volunteering conditions are presented. The study analyzes metacompetences as cognitive, behavioral and emotional aspects leading to more effective behavior in various situations. They are characterized by student’s self-awareness and self-government. The students’ metacompetencies as an educational result of their participation in volunteer activities are considered on the example of the National Research Tomsk State University.